2014
DOI: 10.2139/ssrn.2407873
|View full text |Cite
|
Sign up to set email alerts
|

What are Households Willing to Pay for Better Tap Water Quality? A Cross-Country Valuation Study

Abstract: We estimate willingness to pay (WTP) for better quality of tap water on a unique cross-section sample from 10 OECD countries. On the pooled sample, households are willing to pay 7.5% of the median annual water bill to improve the tap water quality. The highest relative WTP for better tap water quality was found in the countries with the highest percentage of respondents being unsatisfied with tap water quality because of health concerns. The expected WTP increased with income, education, environmental concern,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The literature for example has reported on the importance of water taste compared to odor and color (Doria, 2010;Warren, 1996), on how water users are willing to pay more for better water taste (e.g. Beaumais et al 2010), to reduce water contamination (Cho et al, 2005;Khan, Iqbal, Saeed, & Khan, 2010;Malik et al, 2012) and to be provided with uninterrupted water supply (Baisa et al, 2010;Hensher et al, 2005;Olanrewaju et al, 2012;Vasquez, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature for example has reported on the importance of water taste compared to odor and color (Doria, 2010;Warren, 1996), on how water users are willing to pay more for better water taste (e.g. Beaumais et al 2010), to reduce water contamination (Cho et al, 2005;Khan, Iqbal, Saeed, & Khan, 2010;Malik et al, 2012) and to be provided with uninterrupted water supply (Baisa et al, 2010;Hensher et al, 2005;Olanrewaju et al, 2012;Vasquez, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…According to Doria (2010), organoleptics especially taste relates to sensorial information which affects public's perception of water quality. Beaumais, Briand, Millock, and Nauges's (2010) cross-country valuation study on household's WTP found that respondents who faced problem with taste in water or health concerns related to drinking water are willing to pay higher for better water quality. Doria (2010) noted Warren's (1996) study findings whereby in western countries, water taste is usually more important than odor or appearance, which may due to detection of taste of water chemical at lower concentration than other senses.…”
Section: Willingness To Pay (Wtp) and Determining Factorsmentioning
confidence: 99%
“…A CE was thus selected in order to estimate the social benefits from improved water supply services, because these services can actually be described as a bundle of attributes related to both water quality and water availability characteristics. Other reasons for using the CE method in this study are the following: (1) it can associate the value of a particular good to several individual characteristics, such as income, age, level of education and household composition, which are important factors of households' WTP for improved water quality (Beaumais et al 2010); (2) it is based on questionnaire data that are relatively easy to collect and (3) contrary to CVM studies, it avoids asking directly the WTP for a given good or service. During a period of economic recession, such as the one Greece has experienced over the last 3 years, valuation techniques that elicit values through direct WTP questions are very likely to underestimate environmental goods and services (Latinopoulos 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…As shown inBeaumais et al (2010), a water habit index was constructed by calculating the mean score on the answers related to the values of water use/conservation habits that were elicited by the survey (possible answers were 1 = yes or 0 = no). 7 Fortunately, since nowadays LCM routines are available through statistical packages such as Stata, estimating them should be within the reach of most analysts.…”
mentioning
confidence: 99%